(untitled) (Journal of Economic Research & Business Administration, 2021)
Understanding what controls an individual’s outcome and balancing an individual’s perception of locus of control with work-life has been the major concern over the years. Hence, this study examined the influence of locus of control on the job satisfaction of employees. A survey research design was adopted for this study. A structured questionnaire was administered to collect data from 309 employees of the selected organization. Inferential statistics was used to analyze the data, while the hypotheses were tested by correlation and regression. The result revealed a positive significant effect of work enthusiasm (R2 = 0,576; P = 0,000), psychological states (r = 0,805; P < 0,05), personality traits (R2 = 0,438; P = 0,000) on job satisfaction. The study concludes that locus of control variables are the major determinant of employees’ job satisfaction, and if not properly managed and controlled, it could affect the overall organizational performance. Therefore, managers should ensure the right person with the right emotional and intellectual capabilities are appointed to various positions to forestall employees’ low morale and ineffectiveness. Key words: locus of control, job satisfaction, personality traits, work enthusiasm, reinforcement.